Overview of the sensitivity of Ge- and Al-doped silicon dioxide optical fibres to ionizing radiation - Lim, Tou Ying (Ibnu Sina Institute for Fundamental Science Studies, Universiti Teknologi Malaysia., 2012)
This paper reviews the thermoluminescence sensitivity of Ge- and Al- doped SiO2 optical fibre subjected to various ionizing radiations. It is found that the Ge- doped SiO2 optical fiber has the thermoluminescence response superior to Al-doped SiO2 optical fibre at certain energy and dose range in alpha, beta, photon and electron irradiation. High thermoluminescence intensity per unit dose goes to photon and electron irradiation than alpha and beta irradiation of lower energy. This probably due to the linear energy transfer that influence the dose deposition in the material as incident ionizing radiation striking the surface of Ge- and Al- doped SiO2 optical fibre. However, both doped SiO2 optical fibres show good linearity at studied dose range. It has been proven by researchers providing great potential as a dose absorbed measuring devices especially in radiotherapy energy and dose range